Management of aortic dilatation in Marfan syndrome associated with lung fibrosis - Zenevich, Volha V.; Russu, Maria V.; Myslivets, Marina G.; Direcksze, Naveen D. K. N.; Lamahewa, Thilini K.; Isiwara, Mahima A. H. (International Journal of Contemporary Pediatrics, 2025)
Marfan syndrome (MFS) is an autosomal dominant disorder caused by the mutation in the fibrillin-1 (FBN-1) on chromosome 15q21. The predominant clinical manifestations mainly in ocular, cardiovascular and skeletal system. MFS can also lead to deterioration of lungs progressively over time. In case of lung fibrosis or may be spontaneous in case of spontaneous pneumothorax. Physical examination of this patient revealed the following significant phenotypic manifestations of MFS like scoliosis and skin triae, wrist sign, displaced nasal septum, myopic astigmatism of both eyes pectus carinatum. Furthermore; the computed tomography (CT) scan depicted the fibrotic changes in the lung parenchyma and the echocardiogram depicted the dilation of the aortic root, mitral regurgitation, tricuspid regurgitation. Both X-ray and CT results revealed bilateral lung fibrosis. And the patient was monitored by performing spirometry tests series annually, to detect the evaluation of the prognosis of the patients’ condition. According to the latest publications in MS with interstitial lung disease, this article further reveals the necessity of taking into account the diagnosis of pulmonary manifestations in MS patients with vascular complications. This case illustrates the importance of reviewing the timely management of aortic root dilatation in MFS with lung fibrosis.